2006
DOI: 10.1097/01.inf.0000202130.78540.28
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Haemophilus influenzae Colonization, Antibiotic Resistance and for Sharing an Identical Isolate Among Children Attending 16 Licensed Day-Care Centers in Michigan

Abstract: Although day-care center colonization varied, the overall colonization rate was high. Colonization with nontypable H. influenzae, with beta-lactamase-producing strain and sharing were, mostly, associated with modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Antibiotic use is known to be a major risk factor for the occurrence of resistant bacteria. Several studies have revealed the potential impact of antibiotic use on the increase in the rate of nasopharyngeal carriage of resistant H. influenzae isolates in children (3,6,28,29,40). In our study, the percentage of children who were under treatment for common infantile inflammatory diseases did not differ between the summer and the winter.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Antibiotic use is known to be a major risk factor for the occurrence of resistant bacteria. Several studies have revealed the potential impact of antibiotic use on the increase in the rate of nasopharyngeal carriage of resistant H. influenzae isolates in children (3,6,28,29,40). In our study, the percentage of children who were under treatment for common infantile inflammatory diseases did not differ between the summer and the winter.…”
Section: Discussionmentioning
confidence: 47%
“…The majority of the resistant isolates in our study were low-BLNAR/BLNAR strains, whereas only three isolates (1.7% of all H. infuenzae isolates) were ␤-lactamase positive. In other countries, BLPAR strains are more prevalent, while BLNAR strains are present at low levels; the rates of carriage of BLPAR and BLNAR strains have been reported to be from 3.7 to 55.3% and 0.9 to 2.8%, respectively, in children attending DCCs or living in orphanages (3,5,28,32). In contrast, converse observations have been documented in Japan (11,13,18,34).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The nasopharynx may be colonized by potential pathogens, including Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis (1,6). The opportunistic pathogen Staphylococcus aureus is often found in the anterior nares (20).…”
mentioning
confidence: 99%
“…The second step to address the potential effect of antibiotics on NTHi genetic diversity relied on reanalysis of data from the previously reported study of healthy children in day care centers that included an antibiotic history of each child (2,5). A subset of that study's population, 22 children with at least five NTHi isolates collected, were included in the analysis.…”
mentioning
confidence: 99%